The Impact of CSRD in Shaping Corporate Sustainability and Operational Practices - Ågren, Hanna (My University, 2026)
This thesis addresses how organizations’ structure and governs sustainability reporting practices in response to the Corporate Sustainability Reporting Directive (CSRD), with a focus on sustainability data management, supplier collaboration and information sharing within supply chain networks. The study further aims to increase the understanding of the challenges companies face when integrating sustainability reporting into their supply chain management, including difficulties related to data quality, coordination and cross-organizational collaboration. The study is based on a qualitative research design combining a literature review with semi- structured interviews conducted with representatives from four companies operating in different industries and with varying organizational characteristics. The empirical findings were analyzed using theoretical frameworks related to supply chain networks, sustainable supply chain management and sustainability reporting in supply chain contexts. The findings show that the implementation of CSRD has increased the formalization of sustainability work and strengthened cross-functional collaboration between functions such as sustainability, finance, procurement and risk management. Sustainability reporting is increasingly integrated into governance structures and financial reporting systems, creating a need for new routines connected to data collection, validation and coordination between organizations. Additionally, the study identifies challenges related to data quality, traceability and the integration of sustainability data into operational processes, in particular for information from suppliers beyond tier-1 levels in global supply chains. The findings further demonstrate that companies largely use risk-based approaches in their supply chain governance, where suppliers are prioritized based on sustainability risks and strategic importance. Collaboration with suppliers and industry initiatives is found to be important to improve transparency, harmonize reporting expectations and reduce the administrative burden connected to sustainability reporting. The results also indicate that sustainability reporting is increasingly considered to be more than a compliance requirement and contributes to competitiveness, transparency and long-term business value. The thesis contributes to the understanding of how sustainability reporting requirements under the CSRD are translated into operational practices and governance structures within supply chain networks.
Keywords: Corporate Sustainability Reporting Directive (CSRD); Sustainability Reporting; EU Sustainability Regulation; Sustainable Supply Chain Management; Supply Network Structure; Cross-functional Coordination; Supplier Integration